Review on nanoencapsulated phase change materials: Preparation, characterization and heat transfer enhancement - Liu, Chenzhen; Rao, Zhonghao; Zhao, Jiateng; Huo, Yutao; Li, Yimin (Nano energy, 2015)
In recent years, phase change materials (PCM) which are recommended as potential thermal energy storage medium have been receiving significant attention. The encapsulation technology of PCM is an effective way to enhance the thermal conductivity and solve the issues of leakage and corrosion during the melting process. As a good choice of thermal energy storage materials, the nanoencapsulated phase change materials (NanoPCM) have many advantages, such as small size, large specific surface and high heat transfer rate. Up to now, there has been no complete literature review on the preparation, characterization and application of NanoPCM. In this paper, a comprehensive summary has been presented based on the research of NanoPCM in recent years. The following four aspects have been reviewed in detail: preparation and characterization of NanoPCM, application of NanoPCM in latent functional thermal fluid, dynamics simulation study of NanoPCM and heat transfer enhancement of NanoPCM. It is expected that this review article has certain reference value for the further understanding of NanoPCM. The typical structures of NanoPCM [Display omitted] •Nanotechnology is very important for thermal energy conversion and storage.•Nanoencapsulated phase change material is an effective way to store thermal energy.•Preparation and characterization of nanoencapsulated phase change material are reviewed.•Further research can be conducted on application of nanoencapsulated phase change material.